Open-Source Climate Modeling for Solar and Wind Energy Estimation: Validation with SAM Data and Experimental Measurements - Osama Abdelkawi (International Journal of Management and Data Analytics)
This study assesses the performance of an open-source model in predicting environmental parameters, with a particular focus on bias as the primary evaluation metric. The predictions generated by the current code output are compared with observed data and results from the System Advisor Model (SAM), which utilizes Typical Meteorological Year (TMY) data for the Al-Baha region. The findings reveal that the current code output generally exhibits lower biases across most parameters compared to SAM, underscoring its reliability and adaptability.